The influence of supply chain management practices on supply chain performance: the moderating role of information quality - Bani Hani, Jehad (Business, Management and Economics Engineering, 2022)
Purpose – The main aim of this investigation is to introduce a framework for combining information quality concerning with contextual and representational relevance, and intrinsic accuracy in supply chain management practices to develop supply chain performance in Saudi companies.Research methodology – Inferential technique used to examine the interplay between constructs of the study. SEM was run in order to assess and estimate the causal relationship among variables.Findings – The significant effect of information quality on SCP as well as the significant effect of SCMPs on SCP. Furthermore, it was found that the information quality could significantly moderate the interplay between SCP and SCMPs.Research limitations – This study conducted on 150 Saudi manufacturing companies during the year 2021, in future, the findings can be adapted for other sectors of the Saudi economy.Practical implications – This study has implications for the industrial managers and key personnel. The study provides strong evidence revealing that higher level of integration between SCMPs and quality of information can lead to enhanced supply chain performance.so the proposed model can be used in the practical activities of service sectors In the future; it is possible to change and/ or add key variables and further expand the field of use of the model.Originality/Value – The study contributed in determining main practices of supply Chan management in industrial sector of Saudi Arabia considering their influence on supply chain performance, as well as this study contributed in showing the engagement of information quality in supply chain management.